The effect of counseling based on ex-PLISSIT model on sexual function and marital satisfaction of postpartum women: A randomized controlled clinical trial - Jamileh Malakouti; Robab Golizadeh; Mojgan Mirghafourvand; Azizeh Farshbaf-Khalili (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Since routine counseling does not suffice to resolve the sexual problems at postpartum period, the present study aimed to investigate the effect of counseling based on the Ex-PLISSIT model on sexual function and marital satisfaction of postpartum women. METHODS: This was a randomized controlled clinical trial that was conducted on 68 postpartum women (within 3-6 months after childbirth) who obtained a score <28 on the Female Sexual Function Index (FSFI). The participants were randomly assigned to the intervention and control groups. Participants in the intervention group received counseling based on the Ex-PLISSIT model and those in the control group received the routine postpartum care. The required data were collected using a demographics form, the FSFI, and the ENRICH Marital Satisfaction Scale. The primary outcomes were the mean function and martial satisfaction score of participants 4 and 8 weeks after the intervention. RESULTS: There was no statistically significant difference between the two groups in terms of sexual function at baseline (P = 0.381), but it was significantly higher in the intervention group than control group after intervention (the adjusted MD: 4.24, 95% confidence interval [CI]: 3.18-5.29, P < 0.001). There was no statistically significant difference between the two groups in marital satisfaction before the intervention (P = 0.433), but it increased significantly in the intervention group in comparison to control after intervention (adjusted MD: 23.17, 95% CI: 15.10-31.24, P < 0.001). CONCLUSIONS: The study findings suggested that sexual counseling based on the Ex-PLISSIT model can improve the sexual function and increase marital satisfaction of postpartum women.